Associations of triglyceride-glucose index and metabolic score for insulin resistance with various hypertension phenotypes in children and adolescents: results from the 2017 China nutrition and health surveillance - Zhu, Haiyuan; Yu, Lianlong; Wu, Qiqi; Zhang, Runquan; Zhang, Zebang; Feng, Yumei; Liu, Tao; Liu, Dan; Peng, Jiewen; Chen, Xiongfei; Dong, Xiaomei (Frontiers in Endocrinology, 2025)
BackgroundThe prevalence of hypertension in children is rising globally, with early-onset high blood pressure linked to future cardiovascular risk. Identifying early risk markers beyond obesity and high salt intake is necessary. Although cost-effective indicators of insulin resistance (IR), such as TyG and METS-IR, have been associated with new-onset hypertension in adults, their links with pediatric hypertension, particularly specific phenotypes of hypertension remain unclear.Methods12,087 individuals aged 7–17 years from the 2017 China National Nutrition and Health Surveillance of Children and Lactating Women were included. Hypertension was defined as systolic blood pressure (SBP) and/or diastolic blood pressure (DBP) ≥95th percentile for sex, age, and height. Isolated systolic hypertension (ISH), defined as SBP ≥95th and DBP <95th percentile. Isolated diastolic hypertension (IDH), defined as DBP ≥95th and SBP <95th percentile. Systolic-diastolic hypertension (SDH), defined as both SBP and DBP ≥95th percentile. The associations of TyG and METS-IR with hypertension phenotypes were investigated using multivariable logistic regression and restricted cubic spline regression.ResultsTyG and METS-IR were positively associated with hypertension and all its phenotypes after multivariable adjustment. Treated as continuous variables, each 1-unit rise in TyG corresponds to 44%, 47%, and 61% higher chance of ISH, IDH, and SDH, respectively (odds ratio [OR]: 1.44, 95% confidence interval [CI]: 1.31–1.59; OR: 1.47, 95%CI: 1.21–1.79; OR: 1.61, 95%CI: 1.35–1.91); each 1-unit rise in METS-IR corresponds to 10%, 6%, and 12% higher chance of ISH, IDH, and SDH, respectively (OR: 1.10, 95%CI: 1.09–1.12; OR: 1.06, 95%CI: 1.03–1.08; OR: 1.12, 95%CI: 1.10–1.14). Consistent positive associations were observed across different subgroups for ISH and SDH, whereas this association for IDH was not statistically significant in several subgroups (e.g., age ≥12 years, sufficient sleep, daily exercise). TyG and METS-IR exhibited linear dose-response relationships with all hypertension phenotypes (p-nonlinear >0.10).ConclusionTyG and METS-IR show strong relationships with three kinds of hypertension phenotypes. They are promising markers that may contribute to the primary prevention of hypertension in pediatric populations.